Cuprous-based heat-quenching-resistant fluorescent material as well as preparation method and application thereof

By adopting the use of sub -radical heat resistance and hacked fluorescent materials, the two -dimensional mesh structure is formed, and the problem of losing loss of existing fluorescent powder in high temperature environments has achieved the efficient and stable luminous performance of white light LED. Essence

CN119371676APending Publication Date: 2025-01-28CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411497112.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing high-thermal stability phosphors still have emission losses in high temperature environments, resulting in a decrease in the luminous efficiency of white LEDs, limiting the development of phosphors.

Method used

Using sub -radical anti -thermal heating 荧 fluorescence materials, the chemical formula is [(PMMB) 4CU6I4 (CN) 2] n, and connects N atoms on the cyanomium and ligand PMMB through CU atoms to form a two -dimensional mesh structure to achieve realization and achieve realization. Zero -thermal ingening characteristics.

Benefits of technology

This material shows zero-heat ingenuity within the wide temperature range of 80K-500K, maintaining a stable luminous performance, which significantly improves the optical properties of white light LED, including high-gravity index and low-related color temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371676A_ABST
    Figure CN119371676A_ABST
Patent Text Reader

Abstract

The invention discloses a cuprous-based heat-quenching-resistant fluorescent material as well as a preparation method and application thereof. The chemical formula of the fluorescent material is [(pmmb) 4Cu6I4 (CN) 2] n, and the ligand pmmb is 1, 2-bis ((2-methyl-1H-imidazole-1-yl) methyl) benzene; the fluorescent material belongs to a monoclinic system, the space group is C12 / m1, the cell parameters are # imgabs0 # imgabs1 #, alpha is 90 degrees, beta is 98.596 (3) degrees, gamma is 90 degrees, Z is 2, and the # imgabs2 # comprises the following steps: adding a mixed solvent of CuI, ligand 1, 2-bis ((2-methyl-1H-imidazole-1-yl) methyl) benzene, acetonitrile and water into a reaction kettle, carrying out heating reaction, cooling to room temperature after the reaction is completed, filtering, washing, and drying to obtain the CuI-based fluorescent material. And then filtering, washing and drying to obtain the fluorescent material. The fluorescent material disclosed by the invention shows efficient solid-state emission at room temperature, has high luminous efficiency, shows excellent stability along with the change of temperature, and has a zero thermal quenching phenomenon in a wide temperature range of 80K-500K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optoelectronic functional materials, and in particular to a cuprous-based thermal quenching-resistant fluorescent material and a preparation method and application thereof. Background Art

[0002] At present, there are three main technologies that can achieve white light, depending on the chip: multi-chip white light LED, ultraviolet light-excited white light LED, and blue light-excited white light LED. The mainstream method of blue light-excited white light LED is to combine the blue diode chip with Y3Al5O 12 :Ce 3+ (YAG:Ce 3+ ) yellow phosphor. YAG:Ce 3+ It is an excellent blue light chip excitation phosphor with high photoluminescence quantum yield (QY) and good thermal stability. 3+ The emission spectrum lacks a red component, which poses a challenge to creating white light LEDs with a high color rendering index (CRI, Ra>80) and a low correlated color temperature. To meet this challenge, it is necessary to introduce suitable red light phosphors to supplement the red light component in the LED. In addition, the high operating temperature of the LED often leads to low luminous efficiency of the phosphor, and more excited electrons return to the ground state through non-radiative relaxation. Existing high thermal stability phosphors, such as (Sr,Ca)AlSiN3:Eu2+ and SrSi2O2N2:Eu2+, still have 18% and 20% emission losses at 200°C. The thermal quenching effect changes the balance of white light, which seriously limits the development of phosphors.

[0003] As a cheap metal, cuprous metal is gradually replacing expensive precious metals in many application fields. Its significant cost-effectiveness, especially in the global market environment of tight resources and high costs, has opened up broad application prospects for cuprous metal. Cuprous complexes have received extensive attention in the field of luminescent materials. They have shown great potential in achieving zero thermal quenching characteristics, which is crucial for the manufacture of white light LED devices. Under high temperature conditions, traditional phosphors usually undergo thermal quenching, resulting in reduced luminescence efficiency. However, cuprous complexes with resistance to thermal quenching can effectively resist non-radiative relaxation processes and maintain stable luminescence performance due to their special electronic structure and intramolecular rigidity. This cheapness and resistance to thermal quenching make cuprous complexes ideal materials for the manufacture of high-efficiency white light LEDs, especially in high-power and long-life applications. Summary of the invention

[0004] The first object of the present invention is to provide a cuprous-based thermal quenching-resistant fluorescent material, the technical solution adopted is:

[0005] A cuprous-based thermal quenching-resistant fluorescent material, the chemical formula of which is: [(pmmb)4Cu6I4(CN)2] n , wherein the ligand pmmb is 1,2-bis((2-methyl-1H-imidazol-1-yl)methyl)benzene; the fluorescent material belongs to the monoclinic system, the space group is C1 2 / m 1, and the unit cell parameter is α=90°, β=98.596(3)°, γ=90°, Z=2,

[0006] Furthermore, the Cu + It is four-coordinated, and the metal center of its minimum asymmetric unit structure is [Cu6I4]. The metal center [Cu6I4] is connected to the cyano group and the N atom on the ligand pmmb through its Cu atom to form a two-dimensional network structure.

[0007] The second object of the present invention is to provide a method for preparing a cuprous-based thermal quenching-resistant fluorescent material, the technical solution adopted is:

[0008] A method for preparing a cuprous-based heat-quenching-resistant fluorescent material comprises the following steps: adding CuI, a ligand 1,2-bis((2-methyl-1H-imidazol-1-yl)methyl)benzene, acetonitrile and a mixed solvent of water into a reaction kettle for heating reaction; cooling to room temperature after the reaction is completed; and then filtering, washing and drying to obtain a fluorescent material.

[0009] Furthermore, the molar ratio of the ligand pmmb to CuI is 1:3.5-4.5.

[0010] Furthermore, the volume ratio of acetonitrile to water in the mixed solvent is 2.6-3.6:1; the mass ratio of the mixed solvent to the ligand pmmb is 29-28:1.

[0011] Furthermore, the temperature of the heating reaction is 155° C. to 160° C., and the reaction time is 69 to 72 hours.

[0012] Furthermore, the preparation method of the ligand pmmb is as follows: under nitrogen protection or in air, 2-methylimidazole and (1, (1'-dichloro-o-xylene) are mixed in a methanol solution, and heated to reflux for reaction; after the reaction is completed, the mixture is cooled to room temperature, and the solvent is rotary evaporated to obtain a thick yellow slurry; the yellow slurry is dissolved in a potassium carbonate aqueous solution, and a white solid is generated by standing, and then filtered, washed, and dried to obtain a white powder, which is the ligand pmmb.

[0013] Furthermore, the molar ratio of 2-methylimidazole to 1, (1'-dichloro-o-xylene) is 10.40-10.42:1; the mass volume ratio of 2-methylimidazole to methanol solvent is 0.075-0.076 g / mL, the molar concentration of potassium carbonate aqueous solution is 55-55.5 Mol / L, and the mass volume ratio of 2-methylimidazole to potassium carbonate aqueous solution is 0.0475-0.0476 g / mL.

[0014] Furthermore, the temperature of the heating reflux reaction is 63.8°C to 64°C, and the reaction time is 19 to 20 hours.

[0015] The third object of the present invention is to provide a method for applying a cuprous-based thermal quenching-resistant fluorescent material in a full-spectrum white light LED.

[0016] The fluorescent material of the present invention is combined with a 395nm emitting ultraviolet chip to prepare a multi-component LED and a phosphor-converted white LED (pc-wLED); under the excitation of 395nm ultraviolet light, the LED device integrating the fluorescent material of the present invention and the commercial phosphor shows a near-pure white emission, and has a higher color rendering index and a lower correlated color temperature.

[0017] The fluorescent material of the present invention is made into red light powder, commercial blue light powder BAM, commercial green light powder (Ba, Sr)2SiO4:Eu 2+ The pc-wLED was assembled with a light-emitting diode (LED) and exhibited remarkable optical performance at an operating current of 300 mA: CCT = 4983K, Ra = 88.2, and CIE coordinates (0.3477, 0.3742).

[0018] The beneficial effects of the present invention are:

[0019] (1) The cuprous-based heat-quenching-resistant fluorescent material provided by the present invention exhibits efficient solid-state emission at room temperature, high luminous efficiency, and excellent stability as the temperature changes, and exhibits zero thermal quenching in a wide temperature range of 80K-500K. The fluorescent material of the present invention is made into a red light powder and mixed with commercial blue light powder and commercial green light powder and assembled with a light-emitting diode (LED). The prepared LED exhibits significant optical properties at a working current of 300mA: CCT=4983K, Ra=88.2, CIE coordinates (0.3477, 0.3742), and has great application potential in white light LEDs.

[0020] (2) The preparation method of the present invention has easy-to-obtain synthetic materials, a simple synthesis method and a high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the synthesis of the ligand pmmb of the present invention.

[0022] Figure 2 The diagram shows the synthesis and minimum unit structure of the fluorescent material of the present invention.

[0023] Figure 3 A two-dimensional network structure diagram of the fluorescent material crystal of the present invention; Cu, pink; N, blue; C, gray; hydrogen atoms are omitted for clarity.

[0024] Figure 4 This is the powder X-ray diffraction pattern of the fluorescent material prepared in Example 1.

[0025] Figure 5 This is the infrared spectrum of the fluorescent material and the organic ligand pmmb prepared in Example 1.

[0026] Figure 6 This is the thermogravimetric image of the fluorescent material prepared in Example 1.

[0027] Figure 7 The fluorescence excitation and emission spectra of the fluorescent material prepared in Example 1 at 298K (λem=620nm).

[0028] Figure 8 This is the CIE coordinate diagram of the fluorescent material prepared in Example 1 at 298K.

[0029] Fig. 9 This is a temperature-dependent fluorescence spectrum of the fluorescent material prepared in Example 1.

[0030] Fig.10 This is a temperature-dependent fluorescence emission intensity integral curve of the fluorescent material prepared in Example 1.

[0031] Fig.11 This is the temperature-dependent CIE diagram of the fluorescent material prepared in Example 1.

[0032] Fig.12 This is the EL spectrum of the multi-component pc-wLEDs device at a flux operating current of 10-300mA.

[0033] Fig.13 CIE variation trend diagram for multi-component pc-wLEDs devices.

[0034] Fig.14 Current-dependent EL intensity plot for the multi-component pc-wLEDs device operation.

[0035] Fig.15 This is a graph of the photoluminescence quantum efficiency of the fluorescent material prepared in Example 1 measured at 298K.

[0036] Fig.16This is a fluorescence lifetime decay curve of the fluorescent material prepared in Example 1 at room temperature. DETAILED DESCRIPTION

[0037] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a cuprous-based thermal quenching-resistant fluorescent material and its preparation method proposed by the present invention, its specific implementation method, characteristics and effects are described in detail as follows. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] The reagents involved in the experiment were from manufacturers such as Anage Chemical, Alfa Reagent and Sinopharm Group, and the details are shown in Table 1; the reagents involved were used directly without further purification.

[0039] Table 1 Reagents

[0040] Reagents Specification Manufacturer Acetonitrile Chemically pure Shanghai Lingfeng Reagent Methanol Chemically pure Sinopharm Reagents Distilled water Chemically pure Laboratory-made Cuprous iodide Chemically pure Anaiji Chemical Reagents 2-Methylimidazole Chemically pure Anaiji Chemical Reagents 1, (1'-dichloro-o-xylene) Chemically pure Anaiji Chemical Reagents Anhydrous potassium carbonate Chemically pure Anaiji Chemical Reagents

[0041] The equipment and instruments used in the experiment are shown in Table 2:

[0042] Table 2 Main instruments

[0043]

[0044]

[0045] Example 1

[0046] (1) Under nitrogen protection or in air, 3.8 g, 46.4 mmol, of 2-methylimidazole and 0.78 g, 4.46 mmol, of 1,(1'-dichloro-o-xylene were mixed in 50 mL of a methanol solution and heated under reflux at 80° C. for 20 hours. The reaction was stopped, and after cooling to room temperature, the solvent was rotary evaporated to obtain a thick yellow slurry, which was then dissolved in 6.13 g, 80 mL of an aqueous potassium carbonate solution. The resulting solution was allowed to stand to produce a large amount of crystals, which were filtered off with suction, repeatedly washed with 150 mL of deionized water and filtered, and dried at 70° C. to obtain an organic ligand pmmb, i.e., 1,2-bis((2-methyl-1H-imidazole-1-yl)methyl)benzene.

[0047] The obtained organic ligand pmmb was subjected to carbon nuclear magnetic resonance spectrum analysis: δ=144.83 (Cq), 135.22 (Cq), 128.27 (CAr), 127.26 (CAr), 126.44 (Cimi), 120.86 (Cimi), 46.31 (CH2), 13.04 (CH3).

[0048] (2) 66.5 mg, 0.35 mmol of CuI was mixed with 26.6 mg, 0.1 mmol of the organic ligand pmmb prepared in step (1), 5.5 mL of acetonitrile and 1.5 mL of water, and the mixture was sealed in a 15 mL polytetrafluoroethylene autoclave and reacted at 155° C. for 3 days. After the reaction was completed, it was naturally cooled to room temperature, repeatedly washed with 20 mL of distilled water and 20 mL of acetonitrile, filtered and dried at room temperature to obtain 55 mg of bright yellow crystals, which were fluorescent materials.

[0049] Example 2

[0050] 76 mg, 0.4 mmol of CuI, 26.6 mg, 0.1 mmol of pmmb prepared in Example 1, 6 mL of acetonitrile and 2 mL of water were mixed, and the mixture was sealed in a 15 mL polytetrafluoroethylene autoclave and reacted at 160° C. for 3 days. After the reaction was completed, it was naturally cooled to room temperature, repeatedly washed with 20 mL of distilled water and 20 mL of acetonitrile, filtered and dried at room temperature to obtain 60 mg of bright yellow crystals, which were fluorescent materials.

[0051] Example 3

[0052] 85.5 mg, 0.45 mmol of CuI, 26.6 mg, 0.1 mmol of pmmb prepared in Example 1, 6.5 mL of acetonitrile and 2.5 mL of water were mixed, and the mixture was sealed in a 15 mL polytetrafluoroethylene autoclave, and reacted at 158°C for 3 days. After the reaction was completed, it was naturally cooled to room temperature, repeatedly washed with 20 ml of distilled water and 20 ml of acetonitrile, filtered, and dried at room temperature to obtain 58 mg of bright yellow crystals, which were fluorescent materials.

[0053] The performance test and analysis were carried out using the fluorescent material prepared in Example 1 as an example.

[0054] 1. Crystal phase analysis

[0055] Fluorescent material crystallographic data on an Iuker APEX-IICCD instrument with graphene monochromatic radiation Collected at the corresponding temperature. The two program packages Luker Instrument Servicev4.2.2 and SAINT V8.34 A were used for data collection, data reduction and unit optimization. The structure of the fluorescent material was analyzed using the SHELXS program package, and the crystal data was optimized using the full matrix least squares method using the SHELXL program package. Absorption correction was performed using the multi-scan program package SADABS. The hydrogen atoms of the organic ligands were anisotropically optimized on F2 using the riding mode on the SHELXTL program package. The crystallographic data of the fluorescent material finally obtained are shown in Table 3. Some bond lengths of the fluorescent material The data of bond angle (°) are shown in Table 4. Powder X-ray diffraction analysis: Figure 4 As shown, the red spectrum is drawn from experimental data, and the black spectrum is obtained by computer simulation based on the crystal structure. From the figure, it can be seen that the experimental value and the simulated value of the fluorescent material can match very well, indicating that the fluorescent material is pure phase. Infrared spectrum: IR (KBr pellet, cm-1:): 2071.8 (s), 1591.6 (w). 1538.3 (m), 1501 (m), 1474.9 (m), 1443 (m), 1416.5 (s), 1344.5 (w), 1281.1 (s), 1142.9 (m), 1002.5 (w), 726.1 (s), 667.8 (m). Figure 5 As shown, the red spectrum is drawn from the data obtained from the ligand, and the black spectrum is drawn from the data obtained from the fluorescent material. It can be seen from the figure that the vibration contraction peaks of the ligand and the fluorescent material are almost the same, indicating the presence of organic ligands in the fluorescent material.

[0056] Table 3 Crystallographic parameters of fluorescent materials

[0057]

[0058] a R1=Σ(||F0|-|Fc||) / Σ|F0|; b wR2=[Σw(|F0 2 |-|Fc 2 |) 2 / Σw|F0 2 | 2 ] 1 / 2 ; c GOF=

[0059] [∑[w(F0 2 -Fc 2 ) 2 ] / (Nobs-Nparams)] 1 / 2 ,

[0060] Based on the data I>2σ(I).

[0061] Table 4 Important bond lengths in the crystal structure of fluorescent materials and bond angles()

[0062]

[0063]

[0064] 2. Thermogravimetric analysis

[0065] Thermogravimetric analysis: Figure 6 As shown, the thermal stability of the fluorescent material from room temperature to 800°C was studied. From the TGA curve, it can be seen that the fluorescent material exhibits good thermal stability, and its mass loss is divided into two steps. The first weight loss of the fluorescent material is about 21-22% observed between 100-380°C due to the removal of halogen and part of the ligand. The second weight loss between 380-800°C is 38-39%, and at 800°C, the fluorescent material only loses 50% of its weight, indicating that the fluorescent material has excellent thermal stability.

[0066] 3. Luminous performance test

[0067] Fluorescence test: Figure 7 As shown, the fluorescent material exhibits a strong emission band centered at 620 nm, with a half-maximum width (FWHM) of about 140 nm and CIE coordinates of (0.5518, 0.4399) ( Figure 8 ), which is displayed as orange light. Fig.16 As shown in Figure 2, the PL lifetime is 8.52 μs. In addition, the fluorescent material exhibits excitation band coverage from deep ultraviolet light to blue light. Figure 7 As shown in the fluorescence emission spectrum, the fluorescence emission of the fluorescent material is strongest at an excitation wavelength of 340nm. Photoluminescence quantum efficiency and fluorescence lifetime: The quantum efficiency curve of photoluminescence is shown in Fig.15 As shown in Figure 2, at 298K, the photoluminescence quantum yield (PLQY) of the solid-state fluorescent material is 57.16%. The photoluminescence fluorescence lifetime curve is shown in Figure 2. Fig.16 As shown in Table 5, at 298K, the fluorescence lifetime of the fluorescent material is 8.52μs. r )(k r =Φ PL τ -1 ) is 6.71×10 4 s -1 Considering Φ PL =k r / (k r +k nr ), where knr is the rate of the non-radiative process including non-radiative singlet decay and ISC, k of the fluorescent material nr The value is estimated to be 5.03×10 4 s -1 . Study on fluorescence quenching properties: This invention studies the dependence of fluorescence on temperature, such as Fig. 9 and Fig.10 As shown in the figure, as the temperature gradually increases from 80K to 500K, the fluorescence intensity of the fluorescent material remains stable, without obvious quenching, and the emission center of the fluorescent material has a slight blue shift of about 45nm. The results show that with the change of temperature, the fluorescent material exhibits relatively stable luminescence performance. Fig.11 As shown in Figure 1, as the temperature increases, the luminescence of the fluorescent material changes from orange-red at low temperature (80K) to yellow at high temperature (500K). Correspondingly, the CIE coordinates change from (0.58, 0.3848) at 80K to (0.5221, 0.4549) at 500K. The change in CIE coordinates is consistent with the shift in fluorescence emission as the temperature increases.

[0068] Table 5 Solid-state photophysical data of fluorescent materials at room temperature

[0069]

[0070] a Radiative rate constant calculated k r =Φ / τ. b Nonradiative rate constant

[0071] calculated k nr r=(1-Φ) / τ.

[0072] 4. Device performance test

[0073] Study on the properties of LED devices of fluorescent materials: Considering the high photoluminescence quantum efficiency and thermal stability of fluorescence, the present invention uses ultraviolet chips (λmax = 395nm) to study the LED performance of fluorescent materials. The fluorescent materials of the present invention are made into red light powder and commercial blue light powder BAM, commercial green light powder (Ba, Sr)2SiO4:Eu 2+ Mixed with light-emitting diodes (LEDs) to make multi-component pc-wLEDs devices. The test results of multi-component pc-wLEDs are shown in Figure 12-14 As shown in Table 6-7. Fig.14As shown in Tables 6 and 7, below 300mA, the electroluminescence (EL) intensity of pc-wLEDs increases with the increase of current. The electroluminescence intensity increases 47 times from 10mA to 300mA. The electroluminescence spectrum of white light LEDs based on fluorescent materials covers the entire visible light region of 375-1000nm (i.e., white light emission), such as Fig.14 As shown, the electroluminescence intensity gradually increases in the range of 10-300 mA.

[0074] In order to demonstrate the practical application potential of pc-wLEDs, the color stability at different currents was recorded. Fig.13 As shown in Table 6, CIE x (about 0.3477) and CIE y (about 0.3742) remain basically unchanged in the range of flux current (10-300mA). As shown in Table 6 and Table 7, when the flux current is 300mA, the Ra value of the wLED based on the fluorescent material is as high as 88.2 and the CCT is 4983K. The low CCT and high Ra value show the good optical performance of the pc-wLED at high flux current.

[0075] Table 6 EL parameters of white light LED based on fluorescent materials at different currents

[0076]

[0077] Table 7 EL parameters of white light LED based on fluorescent materials at different currents

[0078]

[0079]

Claims

1. A cuprous-based thermal quenching-resistant fluorescent material, characterized in that: The chemical formula of the fluorescent material is: [(pmmb)4Cu6I4(CN)2] n , wherein the ligand pmmb is 1,2-bis((2-methyl-1H-imidazol-1-yl)methyl)benzene; the fluorescent material belongs to the monoclinic system, the space group is C12 / m1, and the unit cell parameters are α=90°, β=98.596(3)°, γ=90°, Z=2, 2. The cuprous-based thermal quenching-resistant fluorescent material according to claim 1, characterized in that: Cu in crystal + It is four-coordinated, and the metal center of its minimum asymmetric unit structure is [Cu6I4]. The metal center [Cu6I4] is connected to the cyano group and the N atom on the ligand pmmb through its Cu atom to form a two-dimensional network structure.

3. The method for preparing a cuprous-based thermal quenching-resistant fluorescent material according to claim 1 or 2, characterized in that: A mixed solvent of CuI, ligand 1,2-bis((2-methyl-1H-imidazol-1-yl)methyl)benzene, acetonitrile and water is added into a reaction kettle for heating reaction. After the reaction is completed, the mixture is cooled to room temperature, filtered, washed and dried to obtain a fluorescent material.

4. The method for preparing a cuprous-based thermal quenching-resistant fluorescent material according to claim 3, characterized in that: The molar ratio of ligand pmmb to CuI is 1:3.5-4.

5.

5. The method for preparing a cuprous-based thermal quenching-resistant fluorescent material according to claim 3, characterized in that: The volume ratio of acetonitrile to water in the mixed solvent is 2.6-3.6:1; the mass ratio of the mixed solvent to the ligand pmmb is 29-28:

1.

6. The method for preparing a cuprous-based thermal quenching-resistant fluorescent material according to claim 3, characterized in that: The heating reaction temperature is 155°C to 160°C, and the reaction time is 69 to 72 hours.

7. The method for preparing a cuprous-based thermal quenching-resistant fluorescent material according to claim 3, characterized in that: The preparation method of the ligand pmmb is as follows: under nitrogen protection or in air, 2-methylimidazole and (1, (1'-dichloro-o-xylene) are mixed in a methanol solution, and heated to reflux for reaction; after the reaction is completed, the mixture is cooled to room temperature, and the solvent is rotary evaporated to obtain a thick yellow slurry; the yellow slurry is dissolved in a potassium carbonate aqueous solution, and a white solid is generated by standing, and then the solid is filtered, washed, and dried to obtain a white powder, which is the ligand pmmb.

8. The method for preparing a cuprous-based thermal quenching-resistant fluorescent material according to claim 7, characterized in that: The molar ratio of 2-methylimidazole to 1, (1'-dichloro-o-xylene) is 10.40-10.42:1, the mass volume ratio of 2-methylimidazole to methanol solvent is 0.075-0.076 g / mL, the molar concentration of potassium carbonate aqueous solution is 55-55.5 Mol / L, and the mass volume ratio of 2-methylimidazole to potassium carbonate aqueous solution is 0.0475-0.0476 g / mL.

9. The method for preparing a cuprous-based thermal quenching-resistant fluorescent material according to claim 7, characterized in that: The temperature of the heating reflux reaction is 63.8-64°C, and the reaction time is 19h-20h.

10. Use of a cuprous-based thermal quenching-resistant fluorescent material according to claim 1 or 2 in full-spectrum white light LEDs.